Primary surveillance radar (PSR) and secondary surveillance radar (SSR) of martello S743D detection optimization through automatic dependent surveillance-broadcast (ADS-B) adaptation / Abdullah Irfan Abdullah - Abdullah, Abdullah Irfan (2016)
The ADS-B technology is becomes a crucial application for aircraft tracking. An ADS-B system is a system that pinpoint its own position using Global Navigation Satellite System (GNSS) and periodically broadcasts its four-dimensional position 4D (latitude, longitude, altitude and time), track and ground speed, aircraft identification, and other additional relevant data as appropriate without having to be interrogated from a ground station. This thesis highlights how the Primary Surveillance Radar (PSR) and Secondary Surveillance Radar (SSR) of Martello S743D radar detection can be amended by adapting aircraft information retrieved using the Automatic Surveillance - Broadcast (ADS-B) receiver. Such augmentation was achieved through exploitation of the detection information from both sensors; where semblance of information was carried out using the MATLAB Graphical User Interface (GUI). The preliminary findings of the study show that the functional of ADS-B receiver has the potential to mitigate the challenges of "cone of silence" in the PSR and SSR detection.